Murder on Wall Street - Thompson, Victoria (Victoria E.) (Thompson, Victoria (Victoria E.). Gaslight mystery., 2021)
"When a scoundrel is murdered, Sarah and Frank Malloy must find the real killer to stop a scandal that threatens to destroy a young family in this latest installment of the beloved Gaslight Mysteries. The next installment in the beloved Gaslight Mystery series by national bestselling author Victoria Thompson, set in 19th century New York City"--